2016
DOI: 10.1155/2016/7053963
|View full text |Cite
|
Sign up to set email alerts
|

Altered Macrophage and Dendritic Cell Response inMif−/− Mice Reveals a Role of Mif for Inflammatory-Th1 Response in Type 1 Diabetes

Abstract: Macrophage migration inhibitory factor (Mif) is highly expressed in type 1 diabetes mellitus (T1DM). However, there is limited information about how Mif influences the activation of macrophages (Mφ) and dendritic cells (DC) in T1DM. To address this issue, we induced T1DM by administering multiple low doses of streptozotocin (STZ) to Mif−/− or wild-type (Wt) BALB/c mice. We found that Mif−/− mice treated with STZ (Mif−/−STZ) developed lower levels of hyperglycemia, inflammatory cytokines, and specific pancreati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 72 publications
1
11
0
Order By: Relevance
“…MIF characteristics of cell activation and proinflammatory action, make this molecule a constituent element of immunity and stress responses, contributing significantly to several immunopathologies resulting from excessive inflammation and autoimmunity (Donnelly and Bucala, 1997 ; Stosic-Grujicic et al, 2009 ), such as septic shock (Bernhagen et al, 1994 ), arthritis (Morand and Leech, 2005 ), diabetes (Sánchez-Zamora and Rodriguez-Sosa, 2014 ; Sánchez-Zamora et al, 2016 ), and other inflammatory autoimmune conditions (Denkinger et al, 2004 ; Morand, 2005 ; Santos and Morand, 2009 ). Also, the role of MIF in human disease has been recently emphasized since it has been suggested that polymorphisms modifying MIF expression could be associated with severe rheumatoid arthritis, fibrosis and asthma (Baugh et al, 2002 ; Donn et al, 2002 ; Mizue et al, 2005 ; Plant et al, 2005 ; Renner et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…MIF characteristics of cell activation and proinflammatory action, make this molecule a constituent element of immunity and stress responses, contributing significantly to several immunopathologies resulting from excessive inflammation and autoimmunity (Donnelly and Bucala, 1997 ; Stosic-Grujicic et al, 2009 ), such as septic shock (Bernhagen et al, 1994 ), arthritis (Morand and Leech, 2005 ), diabetes (Sánchez-Zamora and Rodriguez-Sosa, 2014 ; Sánchez-Zamora et al, 2016 ), and other inflammatory autoimmune conditions (Denkinger et al, 2004 ; Morand, 2005 ; Santos and Morand, 2009 ). Also, the role of MIF in human disease has been recently emphasized since it has been suggested that polymorphisms modifying MIF expression could be associated with severe rheumatoid arthritis, fibrosis and asthma (Baugh et al, 2002 ; Donn et al, 2002 ; Mizue et al, 2005 ; Plant et al, 2005 ; Renner et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…MIF is released in response to antigenic challenges, such as lipopolysaccharide (LPS) or gram-positive exotoxins, to cytokines such as TNF- α and IFN- γ , as well as physiological stress [16]. Moreover, MIF is an activator of monocytes, Møs, and DCs [1719] and increases phagocytosis and the destruction of intracellular pathogens [20]. The importance of MIF for inflammatory conditions is reflected by the high levels of this cytokine found in patients with diabetes mellitus [19, 21], rheumatoid arthritis [22], multiple sclerosis [23], atherosclerosis [24], asthma [25], inflammatory liver disease [26], ulcerative colitis [27], and cancer [28, 29].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in both DM variants, the proinflammatory cytokine or macrophage migration inhibitory factor Mif, is highly expressed and its level is elevated in the serum. The studies in the mouse model showed that Mif plays a crucial role in macrophages and dendritic cells activation (another type of innate immune system cells), lowers the levels of inflammatory cytokines, hyperglycemia, specific pancreatic islet antigen- (PIAg-) IgG, and reduces macrophages infiltration into the pancreatic islets (Sánchez-Zamora et al 2016 ).…”
Section: Pancreatic Macrophages In Diabetes Mellitus (Dm)mentioning
confidence: 99%